2014
DOI: 10.1186/s12935-014-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

CDK2-AP1 inhibits growth of breast cancer cells by regulating cell cycle and increasing docetaxel sensitivity in vivo and in vitro

Abstract: BackgroundCell cycle regulatory pathway is a well-established pathway mainly dependent on cyclin-dependent kinases (CDKs), which are regulated positively by cyclins and negatively by cyclin-dependent kinase inhibitors(CKIs). Cyclin-dependent kinase 2 associate protein 1(CDK2-AP1) is a specific negative regulatory protein for CDK2, is important in the cancer cell cycle. However, the function of CDK2-AP1 in breast cancer remains unclear. We designed therefore explored the effects of CDK2-AP1 on breast cancer gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
(14 reference statements)
1
15
0
Order By: Relevance
“…Furthermore, pharmacological concentrations of ascorbate could radiosensitize glioblastoma multiforme primary cells by increasing oxidative DNA damage and inhibiting G2/M arrest 35. Unlike the observed increase in cell cycle progression from G1 to S phase driven by cyclin D1, He et al36 found that in breast cancer cells, upregulation of cyclin-dependent kinase 2 associate protein-1 (CDK2AP1) caused cell cycle arrest in G2/M phase and cell division was inhibited. At the same time, there was inverse correlation between CDK2/cyclin D1 and CDK2AP1 expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pharmacological concentrations of ascorbate could radiosensitize glioblastoma multiforme primary cells by increasing oxidative DNA damage and inhibiting G2/M arrest 35. Unlike the observed increase in cell cycle progression from G1 to S phase driven by cyclin D1, He et al36 found that in breast cancer cells, upregulation of cyclin-dependent kinase 2 associate protein-1 (CDK2AP1) caused cell cycle arrest in G2/M phase and cell division was inhibited. At the same time, there was inverse correlation between CDK2/cyclin D1 and CDK2AP1 expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations are in accordance with a wealth of laboratory studies supporting the notion that CDK2AP1 behaves as a tumour-suppressor gene in a variety of tumours (12)(13)(14)(15)(16)(17)(18)(19). Zou et al reported that CDK2AP1 inhibited the proliferation of breast cancer cells and the in vivo growth of tumour cells (15).…”
Section: Discussionsupporting
confidence: 91%
“…CDK2AP1 knockdown resulted in enhanced colony formation and cell growth. It also inhibited the growth of breast cancer cells through regulation of the cell cycle and increased in vitro and in vivo sensitivity to docetaxel (16).…”
Section: Discussionmentioning
confidence: 99%
“…25 When CDKs are abnormally up-regulated, cells undergo cycles and generate resistance to apoptosis, which result in uncontrolled proliferation. 26 CDK2, a member of the CDK family, is a serine/threonine protein kinase. It regulates cell cycle conversion of G1-and S-phase.…”
mentioning
confidence: 99%